miR-20b-5p, TGFBR2, and E2F1 Form a Regulatory Loop to Participate in Epithelial to Mesenchymal Transition in Prostate Cancer - Qi, Jin-Chun; Yang, Zhan; Zhang, Yan-Ping; Lu, Bao-Sai; Yin, Yue-Wei; Liu, Kai-Long; Xue, Wen-Yong; Qu, Chang-Bao; Li, Wei (Frontiers in Oncology, 2020)
The transcription factor E2F1 regulates the expression of the miR-20b-5p precursor and is involved in epithelial-to-mesenchymal transition (EMT). Transforming growth factor-β1 (TGF-β1) induces EMT in prostate cancer (PCa) by binding to TGF-beta receptor 2 (TGFBR2) to activate TGF-β signaling. However, the relationship between TGFBR2, E2F1, and miR-20b-5p in the modulation of EMT in PCa cells remains unknown. In this study, we found that the level of miR-20b-5p expression was significantly lower in PC3 and DU145 cells than that in prostate epithelial (RWPE-1) cells, and TGF-β1 treatment further down-regulated miR-20b-5p expression in these two cell lines. Functional studies showed that miR-20b-5p suppressed TGF-β1-induced migration and invasion of PC3 and DU145 cells by up-regulating E-cadherin and down-regulating vimentin, leading to TGF-β1-induced inhibition of EMT. Using gain and loss of function experiments, it was shown that E2F1 mediated TGF-β1 regulation of miR-20b-5p expression. Further, a luciferase activity assay showed that TGFBR2 was a direct target of miR-20b-5p in PCa cells. These results suggest that miR-20b-5p, TGFBR2, and E2F1 form a regulatory loop to modulate EMT induced by TGF-β1. A novel regulatory mechanism underlying the miR-20b-5p/TGFBR2/E2F1 axis is involved in TGF-β1-induced EMT of PCa cells, and miR-20b-5p may be a potential therapeutic target for PCa.